2012
DOI: 10.1111/ctr.12041
|View full text |Cite
|
Sign up to set email alerts
|

Delayed graft function is not associated with an increased incidence of renal allograft rejection

Abstract: Delayed graft function (DGF) is considered as a risk factor for renal allograft rejection, but this association might be confounded by diagnostic biases (e.g., higher biopsy frequency in patients with DGF, inclusion of clinically diagnosed rejection episodes, and limited details on the rejection phenotype). This retrospective study including 329 deceased donor transplantations aimed to clarify a causal relationship between DGF and rejection. DGF occurred in 93/329 recipients (28%), whereas immediate graft func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“… 2 - 4 , 7 , 15 , 18 , 37 , 44 , 45 Eight studies included living-donor (LD) kidney transplants, 2 , 5 , 32 , 35 , 36 , 43 - 45 and 3 of these studies were restricted to LD transplants only. 36 , 44 , 45 For the rest of the studies, 7 studies included DBD kidneys only, 10 , 18 , 25 , 29 , 31 , 37 , 40 4 studies included DCD kidneys only, 3 , 19 , 30 , 46 whereas 5 studies included both DBD and DCD kidneys, 4 , 7 , 21 , 39 , 42 and 13 studies stated they included DD kidneys without specifying whether it was DBD or DCD. 6 , 8 , 11 , 14 , 15 , 24 , 26 - 28 , 33 , 34 , 41 , 45 One paper included in the review did not specify if donors were LD or DD.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 2 - 4 , 7 , 15 , 18 , 37 , 44 , 45 Eight studies included living-donor (LD) kidney transplants, 2 , 5 , 32 , 35 , 36 , 43 - 45 and 3 of these studies were restricted to LD transplants only. 36 , 44 , 45 For the rest of the studies, 7 studies included DBD kidneys only, 10 , 18 , 25 , 29 , 31 , 37 , 40 4 studies included DCD kidneys only, 3 , 19 , 30 , 46 whereas 5 studies included both DBD and DCD kidneys, 4 , 7 , 21 , 39 , 42 and 13 studies stated they included DD kidneys without specifying whether it was DBD or DCD. 6 , 8 , 11 , 14 , 15 , 24 , 26 - 28 , 33 , 34 , 41 , 45 One paper included in the review did not specify if donors were LD or DD.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 38 studies identified, 30 were single-center studies, [2][3][4][5][6][7]13,14,18,19,21,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] and 8 studies were registry-based studies. 8,10,11,15,[43][44][45][46] Registries included the United States Renal Data System, Scientific Registry of Transplant Recipients, United Network for Organ Sharing, Thai Transplant Registry, the Australia and New Zealand Dialysis and Transplant Registry, NHS Blood and Transplant, and Iran, Kingdom of Saudi Arabia & Kuwait Registry were used by the studies included in our meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the literature, there is a tight relationship between specific immunity and DGF. Many authors have found an association between initial graft dysfunction and higher incidence of rejection crisis .…”
Section: Discussionmentioning
confidence: 99%